Development of Leave Control System V.3 a Case Study from Faculty of Pharmaceutical Sciences, Prince of Songkhla University - Maneewan, Phanutchaya (KKU Science Journal, 2024)
This research aims to develop a Leave Control System Version.3 for the Faculty of Pharmaceutical Sciences, Prince of Songkhla University and evaluate its efficiency and users’satisfaction. The system was designed by applying the principles of the Software Development Life Cycle (SDLC) in this research. The web application was designed base on the Responsive Web Design with Bootstrap, which combined HTML language, JavaScript language and CSS. The system was developed using PHP language and the MySQL database. The developed system was evaluated by users, including 24 academic personnel and 23 administrative personnel. Evaluation of efficiency and overall user satisfaction showed an average score of 4.58 ± 0.52. out of the full score of 5 or at the highest level. In conclusion, the developed system can help solve the problem of redundancy in work, reducing costs, reducing the number of working steps, and reducing data collection problems. The information from the system can be used by the faculty’s personnel to carry out the administrative tasks more efficiently.